Comportamento de cultivares de meloeiro e melancieira em cenários de mudanças climáticas no semiárido brasileiro - Melo, Talyana Kadja de (2019)
The phenology and crop water demand can be altered by climate change, affecting the productivity of major agricultural crops. The objective of this work was to evaluate the futuristic impacts of climate changes (temperature and relative humidity) on the development and evapotranspiration of melon and watermelon varieties cultivated in the Brazilian semi-arid region. The data were obtained from experiments conducted at the Rafael Fernandes Experimental Farm, in the municipality of Mossoró, RN, Brazil. For melon the first experiment was carried out from November 2006 to February 2007, evaluating melon (Cucumis melo L.) type Honey Dew, hybrid cultivar ―County‖. In the second experiment, carried out from October to December of 2008, the melon type Gália hybrid ―Néctar‖ was used. For watermelon the first experiment was carried out from February to April 2006, evaluating the watermelon (Citrullus lanatus) cultivar "Mickylee". In the second experiment, carried out from September to November 2009, the melancholy cultivar "Quetzali" was used. Two emission scenarios based on the Intergovernmental Panel on Climate Change (IPCC) report were evaluated: a optimist named B2 and an pessimist named A2. In the melon it was verified that the climatic changes will cause reduction of on culture development cycle of 15,49 and 25,35% for the hybrid ―County‖ and of 9,84 and 18,03% for the "Nectar" hybrid, considering the optimistic and pessimistic scenarios, respectively. The hybrid ―County‖was more sensitive to climatic changes in the stages intermediate and final, being more susceptible, therefore, to production losses. The climatic changes will increase the coefficient of culture of the melon, increasing the daily evapotranspiration, but with the reduction of the cycle there will be a reduction of the total evapotranspiration. In the watermelon it was verified that the climatic changes will cause reduction in the culture cycle of 14,10 and 26,92% for the cultivar "Mickylee" and of 7,9 and 11,11% for the cultivar "Quetzali", in the optimistic and pessimistic scenarios, respectively. The cultivar "Mickylee" is more susceptible to climatic changes in the stages growth, intermediate and final, being more susceptible, therefore, to production losses. Future climate changes will increase Kc of the melancholy, under the conditions in which the present study was carried out, increasing daily evapotranspiration, and increasing total evapotranspiration, mainly of the cultivar "Mickylee". The changes in temperature and humidity of the air will be outside the limits tolerated by cultures, causing alterations in the cultural dealings, like shading, control of pests and diseases and in the management of the irrigation